The Role of Tour Leaders in Providing Comfort for Umrah Pilgrims at Pt Bina Insani Madinah (BIM Group) Tour & Travel - Ulima Febriani; Achmad Syarifudin; Emi Puspita Dewi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This research is entitled "The Role of Tour Leaders in Providing Comfort for Umrah Pilgrims at PT Bina Insani Madinah (BIM Group) Tour & Travel". The background of this research is based on the complexity of operational challenges such as peak season density, extreme weather, and the diversity of pilgrim backgrounds that demand professionalism of mentoring. This study aims to describe and analyze the role of Tour Leader (TL) in providing comfort to Umrah pilgrims, as well as to find out how this role contributes to the dimension of comfort of pilgrims while in the holy land. The research method used is qualitative descriptive with a case study approach on the Umrah Plus Thaif group departing for the period of December 16, 2025 consisting of 41 pilgrims. Data was collected through in-depth interviews with operational managers as well as Tour Leaders, field observations, and official company documentation. The data analysis techniques applied include data reduction, data presentation, and conclusion drawing based on the Miles and Huberman interactive model. The results show that TL plays a strategic role through personal aspects (emotional stability), behavior (two-door communication and proactive attention), position (facility coordination authority), and expectation (professionalism in compensation management) which contribute directly to the comfort types of Relief, Ease, and Transcendence. The findings prove that TL's professionalism is able to meet four contexts of comfort: physical, psycho-spiritual, environmental, and socio-cultural. In conclusion, the quality of Tour Leader assistance is a key instrument in creating a comfortable worship experience in a holistic manner for pilgrims in the holy land.